A Supramolecular Nanoengine Generates Nanomechanical Force on Demand for Precise Cytosolic Delivery of Anti-miRNAs and Synergistic TNBC Therapy - Yang, Yuxin (Advanced materials (Deerfield Beach, Fla.), 2025)
© 2025 Wiley‐VCH GmbH.